The bullet - Johansen, Iris (New York : Grand Central Publishing, 2021)
Eve Duncan and Joe Quinn must protect the life of a brilliant scientist so that she can live long enough to bring her discovery to the world.
Keywords: Duncan, Eve (Fictitious character) -- Fiction; Facial reconstruction (Anthropology) -- Fiction; Medicine -- Research -- Fiction; Corruption -- Fiction; Thrillers (Fiction)